An Intervention Pattern of Family Parent-Child Physical Activity Based on a Smartphone App for Preschool Children during COVID-19. (22nd August 2022) - Han, Xiaowei; Tian, Zhulin; Zhao, Meiling; Zhou, Zhixiong
Abstract : Objective . Children's lifestyles, behaviors, and educational activities were affected by COVID-19. The preschool children struggled with the challenge of learning at home and avoiding a rapid decrease in physical activity (PA). This study tested the effectiveness of a family-based intervention that integrated the family and preschool based on a smartphone app to improve the moderate-to-vigorous PA (MVPA) and physical fitness of preschool children during COVID-19. Methods . This 8-week study was conducted using a quasiexperimental pre- and posttest design with a comparison group. A total of 66 pairs of preschool children (30 boys) and their parents and 44 preschool children (24 boys) and their parents composed the experimental group (EG) and the control group (CG), respectively. PA was measured using a GENEActiv waveform triaxial accelerometer. Children's physical fitness was assessed using a battery test from the Chinese National Measurement Standards on People's Physical Fitness for preschool children. Results . Preschool children and their parents in the EG participated in less sedentary (p < 0.01 ) and more light PA (p < 0.01 ) and MVPA (p < 0.01 ) compared with those in the CG at the late PA assessment. The EG significantly improved the mean performance of tennis ball throw (p < 0.05 ), balance beam walk (p < 0.01 ), and continuous jumping on both feet (p < 0.01 ) compared to the CG. Conclusions . The family parent-child PA intervention based on a smartphone app can effectively increase the MVPA of preschool children and their parents, reduce sedentary time, and improve preschool children's physical fitness. Overall, the family parent-child PA intervention model based on a smartphone app for preschool children designed in this study is feasible and effective.